2017
DOI: 10.1098/rspb.2017.1383
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early-life competition and maternal nutrition on telomere lengths in wild meerkats

Abstract: Effects of early-life competition and maternal nutrition on telomere lengths in wild meerkats. Proceedings of the Royal Society of London Series B: Biological Sciences, 284(1861), 20171383. (doi:10.1098/rspb.2017.1383 This is the author's final accepted version.There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.http://eprints.gla.ac.uk/147697/ Here, we investigate the link between early-life competition and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
61
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 70 publications
(122 reference statements)
4
61
1
Order By: Relevance
“…A meta‐analysis of 27 studies which measured TL at variable stages suggests that longer telomeres are associated with better survival (Wilbourn et al, ). Similarly, studies which investigate early‐life TL and survival have also demonstrated positive TL effects on short‐term survival (post growth period or fledging in birds (Geiger et al, ; Stier et al, ; Watson, Bolton, & Monaghan, )) or first year survival (Cram, Monaghan, Gillespie, & Clutton‐Brock, ; Salmón, Nilsson, Watson, Bensch, & Isaksson, ) but not always (Boonekamp, Mulder, Salomons, Dijkstra, & Verhulst, ; Cerchiara et al, ; McLennan et al, ; Stier et al, ; Ujvari & Madsen, ; Vedder et al, ). However, because extrinsic factors are always likely to be a major cause of mortality and TL‐associated mortality is likely to diminish with age (Boonekamp, Simons, Hemerik, & Verhulst, ), the predictive effect of early‐life TL on survival may be age‐dependent under natural conditions, a plausible yet untested hypothesis in the wild (Supporting Information Table ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A meta‐analysis of 27 studies which measured TL at variable stages suggests that longer telomeres are associated with better survival (Wilbourn et al, ). Similarly, studies which investigate early‐life TL and survival have also demonstrated positive TL effects on short‐term survival (post growth period or fledging in birds (Geiger et al, ; Stier et al, ; Watson, Bolton, & Monaghan, )) or first year survival (Cram, Monaghan, Gillespie, & Clutton‐Brock, ; Salmón, Nilsson, Watson, Bensch, & Isaksson, ) but not always (Boonekamp, Mulder, Salomons, Dijkstra, & Verhulst, ; Cerchiara et al, ; McLennan et al, ; Stier et al, ; Ujvari & Madsen, ; Vedder et al, ). However, because extrinsic factors are always likely to be a major cause of mortality and TL‐associated mortality is likely to diminish with age (Boonekamp, Simons, Hemerik, & Verhulst, ), the predictive effect of early‐life TL on survival may be age‐dependent under natural conditions, a plausible yet untested hypothesis in the wild (Supporting Information Table ).…”
Section: Introductionmentioning
confidence: 97%
“…Positive associations between early‐life TL and early‐life survival are likely to extend to fitness (e.g., Cram et al, ; Watson et al, ), while this is likely to be true in many cases, life‐history trade‐offs, behaviour, and environmental conditions may obscure this association (Ricklefs & Wikelski, ). If individuals pursue different pace‐of‐life strategies (Ricklefs & Wikelski, ), those with a slower pace‐of‐life may favour self‐maintenance (associated with longer early‐life TL and longer lifespan) over investment in reproductive bouts, resulting in no, or even a negative, association between early‐life TL and fitness.…”
Section: Introductionmentioning
confidence: 99%
“…Telomere length has been linked positively to survival to adulthood and/or annual adult survival probability in both captive (Heidinger et al, ) and wild populations (Asghar, Hasselquist, et al, ; Barrett, Burke, Hammers, Komdeur, & Richardson, ; Cram, Monaghan, Gillespie, & Clutton‐Brock, ; Fairlie et al, ; Haussmann, Winkler, & Vleck, ). Even though other studies have tested for, but not found such associations (Beaulieu, Reichert, Le Maho, Ancel, & Criscuolo, ; Sudyka et al, ), a meta‐analysis in nonhuman vertebrates reported an overall association between short telomeres and higher mortality risk (Wilbourn et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Compelling evidence exists that early‐life conditions such as maternal effects, developmental stress and competition for resources (e.g., Asghar, Bensch, Tarka, Hansson, & Hasselquist, ; Cram et al, ; Haussmann, Longenecker, Marchetto, Juliano, & Bowden, ) can be particularly influential in shaping telomere length. The greater strength of early‐life than late‐life effects could be due to stronger forces of selection, since natural selection acts on the proportion of a cohort that is alive, which is greatest in early‐life (Hamilton, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation